2011
DOI: 10.1001/archneurol.2011.636
|View full text |Cite
|
Sign up to set email alerts
|

The <emph type="ital">APOE</emph> ε2 Allele Increases the Risk of Earlier Age at Onset in Machado-Joseph Disease

Abstract: Background. Machado-Joseph disease (MJD) is an autosomal dominant neurodegenerative disorder of late onset, caused by a (CAG) n expansion at the ATXN3 gene (14q32.1). Variation in age-at-onset is partially explained by the size of the (CAG) n tract in expanded alleles. The remaining variation should be the product of other factors, namely modifier genes. The genotype at the APOE locus has been described as a possible modifier in different neurological disorders, namely Parkinson (PD) and Huntington disease (HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
0
22
2
1
Order By: Relevance
“…The characteristics of this patient cohort are presented in Table 1 . There was no significant difference in the genotypic or allelic distributions of APOE between the present cohort and the cohorts reported by Bettencourt et al [20] (genotype: p = 0.789; allele: p = 0.501) and Peng et al [21] (genotype: p = 0.44; allele: p = 0.872). Patients carrying different APOE genotypes showed no differences in the AAO adjusted for the expanded ATXN3 allele (ANCOVA, F = 0.18, p = 0.9474).…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…The characteristics of this patient cohort are presented in Table 1 . There was no significant difference in the genotypic or allelic distributions of APOE between the present cohort and the cohorts reported by Bettencourt et al [20] (genotype: p = 0.789; allele: p = 0.501) and Peng et al [21] (genotype: p = 0.44; allele: p = 0.872). Patients carrying different APOE genotypes showed no differences in the AAO adjusted for the expanded ATXN3 allele (ANCOVA, F = 0.18, p = 0.9474).…”
Section: Resultscontrasting
confidence: 54%
“…The variability in the AAO attributable to the expanded CAG repeat was calculated using linear regression. Either Fisher's exact test or a chi-square test was used to compare the distribution frequency of APOE genotypes or alleles between our cohort and the cohorts reported by Bettencourt et al [20] and Peng et al [21]. Differences in the AAO according to the APOE genotype and gender of the patient were examined using a two-tailed t-test or an ANCOVA, adjusted for the expanded ATXN3 allele.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to several other neurodegenerative disorders, the TTR gene point mutation alone does not fully determine the AO variation or the course of the disease. Therefore, we have applied, for the first time, a family-centered approach also used in studies of other The role of RBP4 and AR genes in FAP ATTRV30M D Santos et al diseases 19,23 and focused on modifier genes related with (1) TTR functional pathways involved in pathophysiological processes related to FAP ATTRV30M pathogenesis and also (2) sex-linked genes because of observed differences between genders and parent-oforigin effects associated with AO variation. In a previous study, Soares et al 9 analyzed five SNPs (also studied by us) in a Portuguese sample of 92 patients and 85 controls using a classic case-control approach.…”
Section: Discussionmentioning
confidence: 99%
“…The Genetic Modifiers of Huntington's Disease (GeM‐HD) genome‐wide association study (GWAS)6 found two genome‐wide loci associated with age at motor onset in HD on chromosomes 15 and 8, with two independent signals at the same locus on chromosome 15. A few SCA genetic modifiers have been proposed3, 5, 7, 8, 9 and no GWAS have been reported.…”
mentioning
confidence: 99%